Obrona nowożytnej koncepcji praw dziecka. Kilka refleksji w kontekście myśli pedagogicznej Jana Jakuba Rousseau - Małgorzata Kozak (Problemy Wczesnej Edukacji)
The presented text focuses on the normative concept of the rights of the child. The inspiration to re-read this currently dynamic pedagogical and legal category is the persona and ideas of Jean- Jacques Rousseau. The presented reflections are an attempt at a new interpretation of the category of children’s rights in the context of pedagogical naturalism and the rationalism of a philosopher of the Enlightenment. This text may become an argument in defense of the concept of basing the relations between adults and children on the ideas of children’s rights. We are faced with the following question: To what extent does the category of children’s rights, as determined by positive law, and its ensuing implications in terms of children’s status and their relations with adults, result from the nature of man and society, and to what extent do they constitute a mere “pretence of decency”, becoming an enslaving category? Given the degraded nature of man, how can we justify the need to regulate children’s rights and develop education based on these rights, and to what extent do these rights in fact contribute to this degradation, becoming a source of children’s suffering? Contrary to appearances, the answers to these questions are not unequivocal. This text attempts to re-read and re-analyze the fundamental rights of the child set forth in the Convention on the Rights of the Child and the main legal regulations that form its basis with reference to the ideas of the Enlightenment philosopher. The defense of the contemporary concept of children’s rights with reference to the thought of J.J. Rousseau is also a critical voice in the debate on the assumptions, form, and implementation of children’s rights in modern society.